The performance indicators for the state health-related expenditures: Lessons from OECD - Jakub Haas; Eva Gajdošová (European Financial and Accounting Journal, 2016)
The paper deals with the weakness of the Czech public finance - the lack of performance information. The budgeting in the Czech Republic still relies on the incremental method and omits using of performance indicators. On the contrary, most of the OECD member countries has adopted some type of performance budgeting. The paper focuses on the healthcare expenditures of the Czech state budget, analyses long-term experience with performance budgeting in the U.S.A., Australia and New Zealand. It also identifies opportunities and suggests the specific quantitative performance indicators for suitable programmes and organisations of the Ministry of Health.
Keywords: H61; I18; 650; Budgeting; Healthcare; Performance indicators